Frustration and Disclosure Decision-Making: Over-Disclosure or Clam-up? - Themistocleous, Christos (My University, 2023)
The paper is interested on the impact of emotions on consumer disclosure decision-making. Specifically, how induced frustration can affect divulgence decision-making and whether it amplifies over-disclosure or clam-up. Using the visceral states of the hot-cold empathy gap, we compare decisions made between calm and frustrated participants on the fronts of divulgence, accuracy of assessments pertaining to contextually relevant disclosures, and finally customisation (or not) of default options relating to consent for data use.
Keywords: Information Disclosure; Emotions; Nudge Theory